AKTUALISASI PROGRAM KERJA “RUMAH” KREATIFITAS MAHASISWA MELALUI KEGIATAN RIHLAH DAKWAH - irwandi irwandi; Romi Maimori (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2020)
The implementation of the Rihla Dakwah activity is an annual program carried out by the students of Faukulta Ushuluddin, Adab and Da'wah of IAIN Batusangkar which is facilitated by the student's creative "house". The role and students are not only in the form of learning that is carried out on campus but also in the midst of society, through empowerment programs in the religious sector. The implementation of this activity was carried out in Nagari Tabek, Pariangan Dalam District. The research method used is a qualitative research method with a descriptive approach. Qualitative Methods. From this research, it is concluded that the implementation of Rihlah da'wah activities is an implementation of theoretical knowledge learned in tertiary institutions, the level of participation of the Parambah people in activities is very high, and the Rihlah da'wah activity is an Agent of Change forum for students.